2014
DOI: 10.1007/s10143-014-0523-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronic post-traumatic neuropathic pain of brachial plexus and upper limb: a new technique of peripheral nerve stimulation

Abstract: The aim of the study was to evaluate the effect on pain relief in patients with peripheral neuropathic pain after brachial plexus injuries using an implanted peripheral nerve stimulator applied directly to the nerve branch involved into the axillary cavity. Seven patients with post-traumatic brachial plexus lesions or distal peripheral nerve complaining of severe intractable chronic pain were enrolled in a single-centre, open-label trial. Conventional drugs and traditional surgical treatment were not effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…There were no reports of neurological injury. Stevanato et al recently reported an enhanced implantation technique for patients with post‐traumatic brachial plexus injury or distal peripheral nerve lesions with chronic severe intractable neuropathic pain . The authors report that by implanting quadripolar leads proximal to the site of injury and close to the axilla, there was no lead migration or any other complication at 12‐month follow‐up in all seven patients studied.…”
Section: Causation and Reduction Of Neurological Complicationsmentioning
confidence: 94%
“…There were no reports of neurological injury. Stevanato et al recently reported an enhanced implantation technique for patients with post‐traumatic brachial plexus injury or distal peripheral nerve lesions with chronic severe intractable neuropathic pain . The authors report that by implanting quadripolar leads proximal to the site of injury and close to the axilla, there was no lead migration or any other complication at 12‐month follow‐up in all seven patients studied.…”
Section: Causation and Reduction Of Neurological Complicationsmentioning
confidence: 94%
“…Peripheral nerve stimulation provides 50-83% pain relief in 65-80% of the patients [116][117][118][119][120], and the affected limb preserves the residual function remaining after the injury [121]. Allodynia and neuropathic pain are controlled with mild improvement in the sensory function [116,118].…”
Section: Neuromodulation Proceduresmentioning
confidence: 99%
“…In a recent study, Stevanato implanted surgically paddle leads in the axillary cavity in seven patients suffering from chronic post‐traumatic neuropathic pain of BP and upper limb. All the patients reported a pain relief ≥50%, with a mean pain severity improving from nine before surgery to 2.6 at the 12‐month follow‐up . In 2002, Goroszeniuk was the first to implant percutaneously a PNS cylindrical lead in the BP with good results .…”
Section: Discussionmentioning
confidence: 99%
“…Among neuromodulation techniques, both cervical spinal cord stimulation (SCS) and peripheral nerve stimulation (PNS) have been proposed (1,2). Since its first description by Wall and Sweet in 1967 (3), PNS efficacy for chronic neuropathic pain of the upper limbs has been suggested in few isolated cases or short pioneering series reporting variable but encouraging results (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). A combination of peripheral and central mechanisms might explain the analgesic effect induced by low-frequency PNS which preferentially excites large myelinated fibers: modulation of peripheral nociceptors (16), blockade of afferent nociceptive inputs by continuous stimulation (6), modulation of nociception in the dorsal horn of the spinal cord (17).…”
Section: Introductionmentioning
confidence: 99%